1993
DOI: 10.3109/10428199309067940
|View full text |Cite
|
Sign up to set email alerts
|

Possible Imbalance of the Immuno-Hormonal Axis in Multiple Myeloma

Abstract: A comparative study of some immunologic aspects and hormonal balance was performed on 49 multiple myeloma (MM) patients and 29 healthy persons. Functional immunoregulatory imbalances were evident in the majority of patients with MM, as demonstrated by a significant reduction in the mitogenic response of peripheral blood lymphocytes (PBL) to phytohemagglutinin, increased mean stimulation indices of PBL to pisum sativatum agglutinin, wheat germ agglutinin (WGA) and dextran sulphate. Our results appear to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Some epidemiologic associations have also varied by sex; for example, in the European Prospective Investigation on Cancer study, height was associated with increased MM risk among women but not men, and higher weight was associated with increased MM risk among men only (16). These differences could be due to chance, but biochemical studies have reported lower estrogen levels and a decreased estrogen-to-testosterone ratio among women with MM than women without MM (29, 30). These results point to potentially real biological differences in MM risk factors and tumor characteristics by sex.…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiologic associations have also varied by sex; for example, in the European Prospective Investigation on Cancer study, height was associated with increased MM risk among women but not men, and higher weight was associated with increased MM risk among men only (16). These differences could be due to chance, but biochemical studies have reported lower estrogen levels and a decreased estrogen-to-testosterone ratio among women with MM than women without MM (29, 30). These results point to potentially real biological differences in MM risk factors and tumor characteristics by sex.…”
Section: Discussionmentioning
confidence: 99%
“…For multiple myeloma, studies investigated the mechanism of anti-estrogens (AEs), and showed that AEs inhibit cell cycle progression of malignant multiple myeloma cells and/or induce apoptosis in these cells [39]. Other studies suggest that hormone-related and reproductive factors are involved in the etiology of lymphatic malignancies [40], [41], [42], and in a different way for men and women [43], but the results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive activity of the adrenal glands has been documented in human cancer patients with multiple myeloma, 1 chronic lymphocytic leukaemia (CLL) 2–4 and lung and other carcinomas 5 . Increased basal cortisol concentrations, 1–5 adrenal gland enlargement 6 and inadequate adrenal suppression in response to exogenous dexamethasone 5,6 have been documented in various studies. Increased basal cortisol concentrations with lack of suppression in response to dexamethasone was associated with a poorer prognosis following treatment 5 …”
Section: Introductionmentioning
confidence: 99%
“…In certain tumours, continued excessive cortisol secretion has been hypothesized to play a role in cancer initiation or perpetuation 1–3,6 . Although glucocorticoids suppress lymphocyte counts, fluctuations in blood cortisol concentration are necessary to prevent lymphocytic proliferation 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation